Genome-wide linkage analyses and candidate gene fine mapping for HDL₃ cholesterol: the Framingham Study - Yang, Qiong; Lai, Chao-Qiang; Parnell, Laurence; Cupples, L. Adrienne; Adiconis, Xian; Zhu, Yueping; Wilson, Peter W. F; Housman, David E; Shearman, Amanda M; D'Agostino, Ralph B; Ordovas, Jose M (Journal of lipid research, 2005)
High density lipoprotein cholesterol (HDL-C) is inversely associated with coronary heart disease and has a genetic component; however, linkage to HDL-C is not conclusive. Subfractions of HDL, such as HDL₃-C, may be better phenotypes for linkage studies. Using HDL₃-C levels measured on 907 Framingham Heart Study subjects from 330 families around 1987, we conducted a genome-wide variance components linkage analysis with 401 microsatellite markers spaced [approximately]10 centimorgan (cM) apart. Nine candidate genes were identified and annotated using a bioinformatics approach in the region of the highest linkage peak. Twenty-eight single nucleotide polymorphisms (SNPs) were selected from these candidate genes, and linkage and family-based association fine mapping were conducted using these SNPs. The highest multipoint log-of-the-odds (LOD) score from the initial linkage analysis was 3.7 at 133 cM on chromosome 6. Linkage analyses with additional SNPs yielded the highest LOD score of 4.0 at 129 cM on chromosome 6. Family-based association analysis revealed that SNP rs2257104 in PLAGL1 at [approximately]143 cM was associated with multivariable adjusted HDL₃ (P = 0.03). Further study of the linkage region and exploration of other variants in PLAGL1 are warranted to define the potential functional variants of HDL-C metabolism.